A 12-Week Rehabilitation Protocol for the Management of Chronic Extensor Hallucis Longus Rupture Repaired with an Autograft of the Semitendinosus Tendon - Astuti Pitarini; Mitchel; Karina Sylvana Gani; Ratna Moniqa; Erica Kholinne (The Ewha Medical Journal)
Traumatic rupture of the extensor hallucis longus (EHL) is an uncommon finding in an outpatient setting. Surgical repair is typically necessary, particularly in chronic conditions that have persisted for six weeks or more. While several studies have reported EHL repair using autograft tendons, rehabilitation regimes vary, and standardized protocols have not yet been established. This case report presents with an inability to extend her left great toe. She underwent tendon reconstruction with an autograft semitendinosus tendon. At an 8-week follow-up, the patient reported greatly improved outcomes on the American Orthopaedic Foot and Ankle Society, Foot and Ankle Ability Measure, Foot and Ankle Disability Index questionnaire. Full recovery was achieved 12 weeks after surgery. The use of autograft semitendinosus tendon repair for chronic EHL tendon rupture, in conjunction with rehabilitation program, can be expected to yield favorable results.